The Existence of the Mapati Tradition Amidst Islamic Values ​​in Tuban Society - Nurul Farihatun Nisa’; Najma Fauziyatul Mustaghfiroh; Nurul Hakim (Penerbit Hellow Pustaka, 2026)
This study aims to examine the existence of the Mapati tradition in the lives of the Tuban community and to understand how it is maintained amidst the development of Islamic values. The Mapati tradition is a four-month pregnancy ritual imbued with symbolic meaning and prayers for the safety of the mother and unborn child. This study used a qualitative approach with descriptive methods through observation, interviews, and documentation of the local community. The results indicate that the Mapati tradition still exists and continues to be practiced, although it has undergone adjustments to Islamic teachings. Elements of local culture deemed inappropriate are being abandoned, while practices aligned with Islamic values, such as prayer recitation, tahlil (Islamic rituals), and almsgiving, remain. This demonstrates the process of acculturation between local culture and Islamic teachings, creating a distinctive form of religious practice. Thus, the Mapati tradition serves not only as a cultural heritage but also as a medium for integrating social and religious values within Tuban society.